2017
DOI: 10.1007/s12029-017-9937-6
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-Cleaved Cytokeratin 18 Fragment M30 as a Potential Biomarker of Macrovascular Invasion in Hepatocellular Carcinoma

Abstract: The present study suggests that increased M30 fragments of CK18 levels may be useful as a possible marker of early tumor invasiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…4a shows, only CK18, GPC3, and OPN were expressed at a significantly higher level in the no antiviral HCC group compared to the antiviral group. It has been reported that the up-regulation of CK18, GPC3, and OPN are associated with increased tumor aggressiveness and poor prognosis 19,2325 . Then, the IHC scoring was performed by adding the values of the intensity and relative abundance (Materials and Methods), and the average score of such proteins in each group was calculated.…”
Section: Resultsmentioning
confidence: 99%
“…4a shows, only CK18, GPC3, and OPN were expressed at a significantly higher level in the no antiviral HCC group compared to the antiviral group. It has been reported that the up-regulation of CK18, GPC3, and OPN are associated with increased tumor aggressiveness and poor prognosis 19,2325 . Then, the IHC scoring was performed by adding the values of the intensity and relative abundance (Materials and Methods), and the average score of such proteins in each group was calculated.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that elevated M30 CK-18 concentrations may be a useful marker for early stages HCC. Elalfy et al calculated a ROC curve for the M30 CK-18 to discriminate between macrovascular invasions of HCC, which has shown 100% sensitivity and 98% specificity for a cutoff of 304.5 ng/mL (AUC: 0.997, P < 0.001) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…8 (72.7 %) of the studies provided data of M30 expression, and 8 (72.7%) of the studies provided data of M65 expression, while 5 (45.5 %) of them provided data of both. Four (36.4 %) of the studies were in gastric cancer [18][19][20][21], two (18.2 %) studies in HCC [22,23], three (27.3 %) studies in colorectal cancer [24][25][26], and two (18.2 %) in pancreatic cancer [27,28]. The cut-off value of M30 and M65 varies in different studies, ranging from 59.1 U/L to 887 U/L, and from 199.3 U/L to1614 U/L, respectively.…”
Section: Literature Detailsmentioning
confidence: 99%